A framework for password harvesting from volatile memory. (1st January 2012) - Karayianni, Stavroula; Katos, Vasilios; Georgiadis, Christos K.
In this paper, we challenge the widely accepted approach where a first responder does not capture the RAM of a computer system if found to be powered off at a crime scene. We investigate the presence of confidential data in RAM such as user passwords. Our findings show that even if the computer is switched off but not removed from the mains, the data are preserved. In fact, when a process is terminated but the computer is still operating, the respective data are more likely to be lost. Therefore, capturing the memory could be as critical on a switched off system as on a running one.